The prevalence of mitochondrial DNA mutations in Leigh syndrome in a Brazilian series - Marie,Suely Kazue Nagahashi (2014)
OBJECTIVE: To determine the prevalence of mitochondrial DNA (mtDNA) mutations in cases with ﬁndings compatible with the diagnosis of Leigh syndrome in a Brazilian Neurological Service, and to compare those ﬁndings between the patients presenting or not these mutations. METHOD: We analyzed six mtDNA point mutations (T8993G, T8993C, T8851C, G1644T, T9176C, and T3308C) by PCR and endonuclease digestion in 32 patients with presumptive diagnosis of Leigh syndrome, according to distribution across different age ranges. RESULTS: We found two patients, in the subgroup under 4 years of age, presenting T8993G and T8993C mutations. Their clinical symptoms and neuroimaging ﬁndings were similar when compared to those patients not harboring these mutations. CONCLUSION: As the molecular conﬁrmation is pivotal for both the precise genetic counselling and therapeutic guidance, we emphasise the beneﬁt of screening for mtDNA mutation in Leigh syndrome patients under 4 years old. Mitochondrial whole genome and whole exome analysis by next-generation sequencing technology maybe a future alternative for molecular diagnosis of this extensive genetic heterogeneous syndrome.